2005
DOI: 10.1007/s10584-005-5358-9
|View full text |Cite
|
Sign up to set email alerts
|

Standardized Precipitation Index Reconstructed from Turkish Tree-Ring Widths

Abstract: May-July Standardized Precipitation Index (SPI) for the land area of most of Turkey and some adjoining regions are reconstructed from tree rings for the period 1251-1998. The reconstruction was developed from principal components analysis (PCA) of four Juniperus excelsa chronologies from southwestern and south-central Turkey and is based on reliable and replicable statistical relationships between climate and tree ring growth. The SPI reconstruction shows climate variability on both interannual and interdecada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 102 publications
(66 citation statements)
references
References 29 publications
6
59
0
1
Order By: Relevance
“…Table IV compares extreme dry and wet years identified in our reconstructions with those found in other tree-ring reconstructions and chronologies for Turkey (Kuniholm, 1996;D'Arrigo and Cullen, 2001;Touchan et al, 2003Touchan et al, , 2005aHughes et al, 2001), as well as historical archives (Purgstall, 1983;Panzac, 1985; Ottoman Archives of the Prime Minister of Turkey, 1850Turkey, -1923Inalcik, 1997).…”
Section: Comparison With Other Turkish Reconstructions and Historicalmentioning
confidence: 78%
See 3 more Smart Citations
“…Table IV compares extreme dry and wet years identified in our reconstructions with those found in other tree-ring reconstructions and chronologies for Turkey (Kuniholm, 1996;D'Arrigo and Cullen, 2001;Touchan et al, 2003Touchan et al, , 2005aHughes et al, 2001), as well as historical archives (Purgstall, 1983;Panzac, 1985; Ottoman Archives of the Prime Minister of Turkey, 1850Turkey, -1923Inalcik, 1997).…”
Section: Comparison With Other Turkish Reconstructions and Historicalmentioning
confidence: 78%
“…Hughes et al (2001) found that extreme signature years in tree-ring data from the Aegean region (including northern Turkey, Greece and Georgia) coincided with recorded April-June precipitation and sea level pressure anomalies. Touchan et al (2003Touchan et al ( , 2005a demonstrated correspondence between Turkish tree-rings and atmospheric circulation patterns during extreme years. Although Touchan et al's study partly overlaps that reported herein, they did not include data from our immediate north-western Turkey study region.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…In the literature, several recent dendroclimatological studies have focused on analysing droughts in the eastern Mediterranean (e.g. Akkemik, 2000;Touchan et al, 2003Touchan et al, , 2005Touchan et al, , 2007Akkemik et al, , 2008; however, few studies have considered the analysis of droughts in the region of Jordan (e.g. Touchan et al, 1999).…”
Section: Introductionmentioning
confidence: 99%